Reconocemos formas geométricas en los objetos - Juarez Vega, Edith del Milagro (2018)
This lesson plan is important because it is going to allow students to learn from their needs and lively experiences. At the momento of plant and solve problems, students face themselves to new challenges. It helps that students get interest and motivation when they play and put in practice observations direct from the space through their senses. Learn geometrical forms represent the previous step to learning geometry and spacial reasoning. This lesson plan allow students to recognize objects with tridimensional forms: roll and not roll, rounded and plains.